The everything STEM handbook : help your child learn and succeed in the fields of science, technology, engineering, and math - Sawah, Rihab (Everything series., 2015)
"Projects and experiments to inspire and challenge your kids! The STEM fields (science, technology, engineering, and math) are top education priorities in the United States--and they are growing fields with a high demand for jobs. If you want to make sure your children are prepared for the future in these fields, here's how you can help: Make it fun! Expose them to hands-on, real-world, and fun activities so they'll become engaged, motivated, and successful students later on. Look inside for ideas and activities to stimulate your child's interest in these fascinating subjects, including: Racing juice cans Setting up a circuit Observing potato osmosis Building a mousetrap race car Creating a Cartesian treasure map Going on a geometry scavenger hunt Building a bridge Exploring food chemistry With easy-to-understand examples, problem-solving tips, and hands-on projects your family can create together, this guide gives you the tools you need to help your kids excel and foster a lifetime love of learning"--